Gender, Culture And The Use Of Information And Communication Technology In Botswana - Mangadi, Tebogo Ruth (2004)
The study was undertaken to evaluate the extent of the digital divide along gender lines in our secondary education systems. The findings of this study beae a remarkable similarity to other studies that examined the relationship between gender and the use of ICTs.